Naming, Blaming, Erasing: Van Leeuwen’s Recontextualization–Legitimation Matrix in Bratang Surabaya Coverage, 20 August 2025 - Shofah, Novia Adibatus; Indriyani, Jiphie Gilia; Atikurrahman, Moh; Abdullah, Asep Abbas (SULUK : Jurnal Bahasa, Sastra, dan Budaya, 2025)
This study examines how nine Indonesian online outlets transformed the 20 August 2025 Taman Flora–Bratang traffic accident in Surabaya into stabilised news narratives. Using Theo van Leeuwen’s socio-semiotic framework and a mixed-methods Critical Discourse Analysis, we ask: (1) how actors, actions, time–space, purposes, and legitimations are added or removed; (2) how victims, the car/driver, police, and “road/space” are portrayed (naming, genericisation, activation/passivation, inclusion/exclusion); and (3) which authorisation, moral evaluation, rationalisation, and mythopoesis assign responsibility under breaking-news uncertainty. A parallel, convergent analysis treated sentences (including headlines) as units across nine same-day reports. Quantitatively, we tracked inclusion/exclusion, activation/passivation, gender marking, and legitimation types per sentence; qualitatively, we traced outlet-level patterns via a CDA Matrix, joint displays (actor × legitimation), and a recontextualisation flow. Double-coding (Cohen’s κ template) audited heuristic labels, with discrepancies resolved interpretively. Three recurring narrative packages emerged: (i) a police-led “two-motor” template that simplifies causality and backgrounds the car/driver; (ii) a BPBD-led procedural timeline that individualises the driver yet defers legal judgment; and (iii) a defensive naming-then-denial pattern specifying the car (even plate/model) while disassociating it via surface forensic cues. Early texts privilege authorisation (police/BPBD voice) and rationalisation (procedural/technical accounts); moral cues and mythopoetic framings surface subtly in headlines. Social-actor design personalises/feminises the deceased and functionalises authorities, pre-structuring responsibility maps.